Optimizing Early Childhood Education Management: Designing SISPAUD KB Ananda using End User Development (EUD) Method - Suryadilaga, Salli Risqi Warida; Raras AW, Chyntia; Pritama, Argiyan Dwi; Islamindiya, Syifa Fauziyah Nurul (PT Mattawang Mediatama Solution, 2024)
Early childhood education at PAUD KB Ananda aims to develop knowledge and skills. To support this goal, PAUD KB Ananda has an online information system,